English English - Lembang, Alviona Anggita Rante; Nababan, Natanael Andra Jaya; Latifiani, Dian (Faculty of Law, Universitas Slamet Riyadi, 2022)
The absolute authority of the Religious Courts can be seen from Law Number 7 of 1989 in conjunction with Law Number 3 of 2006 concerning Religious Courts. Meanwhile, the District Court has the authority to examine, hear, and decide criminal and civil cases at the first level. Both the Religious Courts and the District Courts are authorized to settle inheritance disputes. Law No. 3 of 2006 concerning the Religious Courts states that for Muslims, the institution to settle inheritance cases is the Religious Courts. Meanwhile, non-Muslims can apply for dispute resolution to the District Court. However, the absolute authority of the Religious Courts still gives Muslim people a choice of law to choose what law to use in resolving inheritance disputes occurred which gives the potential to cause a conflict of authority between the two judicial institutions. Therefore, this conlifct must be resolved in order to create legal certainty